Natural History of Clinical, Laboratory, and Echocardiographic Parameters of a Primary Hyperoxaluria Cohort on Long Term Hemodialysis - Sas, David J.; Enders, Felicity T.; Gunderson, Tina M.; Mehta, Ramila A.; Olson, Julie B.; Seide, Barbara M.; Banks, Carly J.; Dehmel, Bastian; Pellikka, Patricia A.; Lieske, John C.; Milliner, Dawn S. (Frontiers in Medicine, 2021)
Background: Primary hyperoxaluria type 1 (PH1) is a rare monogenic disorder characterized by excessive hepatic production of oxalate leading to recurrent nephrolithiasis, nephrocalcinosis, and progressive kidney damage, often requiring renal replacement therapy (RRT). Though systemic oxalate deposition is well-known, the natural history of PH1 during RRT has not been systematically described. In this study, we describe the clinical, laboratory, and echocardiographic features of a cohort of PH1 patients on RRT. Methods: Patients with PH1 enrolled in the Rare Kidney Stone Consortium PH Registry who progressed to require RRT, had ≥2 plasma oxalate (pOx) measurements 3–36 months after start of RRT, and at least one pair of pOx measurements between 6 and 18 months apart were retrospectively analyzed. Clinical, echocardiographic, and laboratory results were obtained from the Registry. Results: The 17 PH1 patients in our cohort had a mean total HD hours/week of 17.4 (SD 7.9; range 7.5–36) and a range of age of RRT start of 0.2–75.9 years. The average change in plasma oxalate (pOx) over time on RRT was −0.74 [−2.9, 1.4] μmol/L/month with the mean pOx never declining below 50 μmol/L. Over time on RRT, oxalosis progressively developed in multiple organ systems. Echocardiography performed on 13 subjects showed worsening of left ventricular global longitudinal strain correlated with pOx (p < 0.05). Conclusions: Even when a cohort of PH1 patients were treated with intensified RRT, their predialysis pOx remained above target and they developed increasing evidence of oxalosis. Echocardiographic data suggest that cardiac dysfunction could be related to elevated pOx and may worsen over time.